Design a Novel Reverse Direction Transmission Using Piggyback and Piggyback With Block ACK to Improving the Performance of MAC Layer Based on Very High Speed Wireless LANs - -, Ali Ahmad Milad; Muhamad Noh, ZulAzri; Shibghatullah, Abdul Samad; -, Mustafa Almahdi Algaet (2013)
A reverse direction transmission and block acknowledgement are the main features to improve the performance of MAC layer based on next generation wireless LANs. When the data send it in reverse direction from side A to B, side B does not need to send separate ACK, it may wait for a period of time is less than the sender’s time of period to avoid the retransmission at sender and send a piggyback frame (ACK+data) this called piggybacking. Piggyback with block ACK represented in multi data send from side A to B with block ACK request (BAR), side B send block ACK (BA) piggybacking with multi data to side A, this called piggybacking with block ACK. In our scheme here we want to propose a novel reverse direction transmission using piggyback and piggyback with block ACK which is divided each data frame send and receive into subframes and send each subframe separately, if there is an error happened during the transmission only retransmission the corrupted subframe instead of whole frame. We want to implement this work in NS2 simulator. The research contributions are summarized and the piggyback schemes that need to be investigated via high speed wireless LANs are also highlighted.